If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+(x+4)=(2+x)+4
We move all terms to the left:
2+(x+4)-((2+x)+4)=0
We add all the numbers together, and all the variables
(x+4)-((x+2)+4)+2=0
We get rid of parentheses
x-((x+2)+4)+4+2=0
We calculate terms in parentheses: -((x+2)+4), so:We add all the numbers together, and all the variables
(x+2)+4
We get rid of parentheses
x+2+4
We add all the numbers together, and all the variables
x+6
Back to the equation:
-(x+6)
x-(x+6)+6=0
We get rid of parentheses
x-x-6+6=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| n÷8-4=-7 | | 2x+3+3x-1=52 | | -3(-2b-1)=21 | | (5/4)x+7=13+x | | 2m-44=76-8mm= | | 25=4n-3n= | | 2a+2a+4=20 | | h(3)=2^3 | | 5+4n=13n= | | (10+2x)/3=4x= | | 2x=15x= | | 2+x=7x-15 | | 6x-+2=4x+10 | | 11*x+35=15*x | | 11+3m*6=42m-13 | | 100=3^x | | 18/x=x/50 | | 2(x+4)=(x+4)2 | | 10h/20=0.5 | | 2,5/1,24=x/6,2 | | 25x+29=-3 | | 4x-30=x*6 | | 4m-3=13(m-4) | | 18x-3=5x+8 | | 6.6x-60=20+6x | | a2=836 | | B+8+2b+7+b+b=6b+3 | | b2=128 | | 2+3m-9=-7 | | 1.4+x÷6=2.4 | | 3a-4+7a+10=126 | | 180=3y |